An evaluation of scintillation index in atmospheric turbulent for new super Lorentz vortex Gaussian beam - Hussein Thary Khamees; Ahmed Saad Hussein; Nadhir Ibrahim Abdulkhaleq (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2023)
Super Lorentz vortex Gaussian beam (SLVGB) is propagated via the turbulent atmosphere parameters. The benefit key of the SLVGB wave model is that the unlimited bandwidth wave and a spherical wave are involved. Additionally, Huygens Fresnel integral was used for schoolwork to study the propagation of SLVGB in a slant direction via a moderate turbulent medium. On the other hand, applying the crude international telecommunication union (ITU-R) model possible. Moreover, the Kolmogorov turbulent power spectrum model is applied, and the source field is dispersed by the zenith angle to the receiver plane. Additionally, examine the contour of the source field and the SLVGB intensity. To investigate various parameters such as source size, mode, scintillation index, topological charge, and others that are associated with the beam of super Lorentz vortex Gaussian are entirely understood, the outcomes were examined, and obtained other references to build the beam of slant path propagation in turbulent; the form constants are especially in comparison and matching. Our graphical findings indicate that the parameters happened randomly in the scintillation index and intensity of the SLVGB, resulting in a novel beam technical configuration. To summarize, this article is advantageous for remote sensing and uses an optical communications system and laser applications.